STRATEGI KEKUATAN LOGISTIK UNTUK MENINGKATKAN KINERJA DI SEKTOR INDUSTRI PAKAIAN JADI - Rindang Matoati; Rr. Siti Muslikhah; Nisa Zahra; Eka Noviani Azis; Akasyah Palahuddin (Universitas Ahmad Dahlan, 2016)
In modern era, there is a change in human basic needs for apparel that willmake business in fashion industry become interesting dan increasing siginifi cantly. The growth of apparel industry contributes wealth enhancement of the stakeholders, starting from suppliers, small producers to big producers -such as small medium entreprises to national companies, and distributors. But there are also some obstacles faced by those stakeholders that slower their improving performance in Indonesia’s apparel industry development such as logistics problem, especially in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) area. The purposes of this research are: 1) To identify the strengths, weaknesses, opportunity and threat of logistics in apparel industry, 2)To formulate strategy to advantage the power of logistics as an effort to improve apparel industry performance in Jabodetabek area. This research took place in Jabodetabek, Indonesia. SWOT analysis and AHP method were used to analyze the data. The results of this research is aimed to provide a right management strategy of logistics to improve apparel industry performance in Jabodetabek.